(untitled) (Research, Society and Development, 2022)
Introduction: Children with neuromotor disorders have reduced social participation, impacts on their diverse occupations, as well as limited repertoire compared to their peers with typical development. Objective: This study aimed to present actions in Occupational Therapy using the Bobath concept with children with neuromotor and developmental disorders and the strategies used to promote functionality and participation in their main occupations. Method: This article is an experience report developed in an extension project called: Occupational Therapy and Pediatric Bobath concept: assistance to children with neuromotor disorders. All the processes of the therapeutic practice were described, from the assessment protocols, therapeutic plans, definition of objectives, in order to identify the functional capacities and deficiencies of the patients attended, to be able to base their planning and intervention on the approach of solving problems. Results: It was observed that few studies have proposed to investigate and make visible what has been adopted in terms of rehabilitation strategies in Occupational Therapy in the care of children with neuromotor disorders and within the autistic group. Conclusion: We recognize that this is an experience report with a university outpatient approach, but that it can contribute to the addition of studies and clinical trials in order to disseminate what occupational therapy can and have used as strategies for a more public heterogeneous within the Bobath concept, as well as clarifying what differentiates us from the physiotherapy and speech therapy professionals who work with the Bobath concept in terms of technical actions.